Evaluation of developmental changes in bovine in vitro produced embryos following exposure to bovine Herpesvirus type 5 - Brenner Mariana PC; Silva-Frade Camila; Ferrarezi Marina C; Garcia Andrea F; Flores Eduardo F; Cardoso Tereza C (BMC, 2012)
Abstract Background Bovine Herpesvirus type-5 (BoHV-5) is a neurovirulent α-Herpesvirus which is potentially pathogenic for cows and suspected to be associated with reproductive disorders. Interestingly, natural transmission of BoHV-5 by contaminated semen was recently described in Australia. Additionally, BoHV-5 was also isolated from the semen of a healthy bull in the same country and incriminated in a natural outbreak of reproductive disease after artificial insemination. In contrast with BoHV-1, experimental exposure of in vitro produced bovine embryos to BoHV-5 does not affect embryo viability and seems to inhibit some pathways of apoptosis. However, the mechanisms responsible for these phenomena are poorly understood. In this study, we examined mitochondrial activity, antioxidant protection, stress response and developmental rates of in vitro produced bovine embryos that were exposed and unexposed to BoHV-5. Methods For this purpose, bovine embryos produced in vitro were assayed for cell markers after experimental infection of oocytes (n = 30; five repetitions), in vitro fertilization and development. The indirect immunofluorescence was employed to measure the expression of superoxide dismutase 1 (SOD1), anti-oxidant like protein 1 (AOP-1), heat shock protein 70.1 (Hsp 70.1) and also viral antigens in embryos derived from BoHV-5 exposed and unexposed oocytes. The determination of gene transcripts of mitochondrial activity (SOD1), antioxidant protection (AOP-1) and stress response (Hsp70.1) were evaluated using the reverse transcriptase polymerase chain reaction (RT-PCR). MitoTracker Green FM, JC-1 and Hoechst 33342-staining were used to evaluate mitochondrial distribution, segregation patterns and embryos morphology. The intensity of labeling was graded semi-quantitatively and embryos considered intensively marked were used for statistical analysis. Results The quality of the produced embryos was not affected by exposure to BoHV-5. Of the 357 collected oocytes, 313 (+/− 6.5; 87,7%) were cleaved and 195 (+/− 3.2; 54,6%) blastocysts were produced without virus exposure. After exposure, 388 oocytes were cleaved into 328 (+/− 8.9, 84,5%), and these embryos produced 193 (+/− 3.2, 49,7%) blastocysts. Viral DNA corresponding to the US9 gene was only detected in embryos at day 7 after in vitro culture, and confirmed by indirect immunofluorescence assay (IFA). These results revealed significant differences (p < 0.05) between exposed and unexposed oocytes fertilized, as MitoTracker Green FM staining Fluorescence intensity of Jc-1 staining was significantly higher (p < 0.005) among exposed embryos (143 +/− 8.2). There was no significant difference between the ratios of Hoechst 33342-stained nuclei and total cells in good-quality blastocysts (in both the exposed and unexposed groups). Using IFA and reverse transcriptase polymerase chain reaction (RT-PCR) for the set of target transcripts (SOD1, AOP-1 and Hsp 70.1), there were differences in the mRNA and respective proteins between the control and exposed embryos. Only the exposed embryos produced anti-oxidant protein-like 1 (AOP-1). However, neither the control nor the exposed embryos produced the heat shock protein Hsp 70.1. Interestingly, both the control and the exposed embryos produced superoxide dismutase (SOD1), revealing intense mitochondrial activity. Conclusion This is the first demonstration of SOD1 and AOP-1 production in bovine embryos exposed to BoHV-5. Intense mitochondrial activity was also observed during infection, and this occurred without interfering with the quality or number of produced embryos. These findings further our understanding on the ability of α-Herpesviruses to prevent apoptosis by modulating mitochondrial pathways.